PENERAPAN MODEL PEMBELAJARAN KOOPERATIF SNOWBALL THROWING UNTUK MENINGKATKAN KEAKTIFAN BELAJAR SISWA MATERI SEGITIGA DI KELAS V GMIT KUANINO 1 KUPANG - Betris Sani Helvin, Magdalena; Sabon Dominikus, Wara; Bol Nifu Benu, Adam (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low level of learning activeness among fifth-grade students of SD GMIT Kuanino 1 on the topic of triangles, as indicated by their limited participation in asking and answering questions, expressing opinions, and engaging in classroom discussions during the learning process. The purpose of this study was to improve students' learning activeness through the implementation of the Snowball Throwing cooperative learning model. This study employed Classroom Action Research (CAR) conducted in two cycles using the Kemmis and McTaggart model, which consists of planning, action, observation, and reflection stages. The subjects of the study were 16 fifth-grade students of SD GMIT Kuanino 1 Kupang. Data were collected through observation, questionnaires, and documentation, and were analyzed using descriptive quantitative techniques. The results showed that the implementation of the Snowball Throwing cooperative learning model improved students' learning activeness. Based on observation results, the average percentage of students' learning activeness increased from 62.63% in Cycle I, categorized as active, to 85.16% in Cycle II, categorized as very active, resulting in an increase of 35,97 percentage points. The questionnaire results also indicated an improvement in students' learning activeness and positive responses toward the implementation of the Snowball Throwing learning model. Students became more active in asking and answering questions, participating in discussions, collaborating with group members, and completing learning tasks. Therefore, the Snowball Throwing cooperative learning model is effective in improving students' learning activeness in mathematics learning on the topic of triangles